2021
DOI: 10.1136/heartjnl-2021-319063
|View full text |Cite
|
Sign up to set email alerts
|

Change in N-terminal pro-B-type natriuretic peptide at 1 year predicts mortality in wild-type transthyretin amyloid cardiomyopathy

Abstract: ObjectivesWild-type transthyretin amyloid cardiomyopathy (wtATTR-CM) is a progressive and fatal condition. Although prognosis can be determined at the time of diagnosis according to National Amyloidosis Centre (NAC) transthyretin amyloidosis (ATTR) stage, the clinical course varies substantially between individuals. There are currently no established measures of rate of disease progression. Through systematic analysis of functional, biochemical and echocardiographic disease-related variables we aimed to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Similar results, in term of reduction of TTR levels, were reported in patients receiving Inotersen in the NEURO TTR study [76]. Recently, Law et al [77] reported that change in NT-proBNP concentration, during the first year of follow-up, is a powerful independent predictor of mortality in a large cohort of patients with untreated wtATTR-CM. The authors emphasize that the prognostic relevance of the NT-proBNP changing was independent of NAC ATTR stage, troponin T, age, NYHA class, 6MWT distance, presence of atrial fibrillation and interventricular septal thickness at echocardiography.…”
Section: Attr Amyloidosissupporting
confidence: 73%
“…Similar results, in term of reduction of TTR levels, were reported in patients receiving Inotersen in the NEURO TTR study [76]. Recently, Law et al [77] reported that change in NT-proBNP concentration, during the first year of follow-up, is a powerful independent predictor of mortality in a large cohort of patients with untreated wtATTR-CM. The authors emphasize that the prognostic relevance of the NT-proBNP changing was independent of NAC ATTR stage, troponin T, age, NYHA class, 6MWT distance, presence of atrial fibrillation and interventricular septal thickness at echocardiography.…”
Section: Attr Amyloidosissupporting
confidence: 73%
“…A formal bias assessment of identified studies is provided in online supplementary Table . The individual studies and the extracted aggregate data are summarized in Table 2 2,3,10,11,13,26,27,29,30,52,54,65,71,78–158 . An exponential growth in the annual publication of studies on clinical outcomes of ATTR was observed over the recent years ( Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Blood biomarker studies to date have mainly focused on wtATTR-CM. 2 Echocardiography typically offers the first clues to diagnosis of ATTR-CM and its prognosis. [3][4][5][6][7] However, whilst its value for diagnosis and prognosis at patients' initial presentation has been established, 8 the role of serial echocardiography to ascertain and elucidate the basis for disease progression within individuals has been little studied.…”
Section: Introductionmentioning
confidence: 99%
“…However, the natural history remains poorly understood as are the most clinically meaningful parameters acquired by serial echocardiography, which is nevertheless performed routinely to monitor disease progression. Blood biomarker studies to date have mainly focused on wtATTR‐CM 2 …”
Section: Introductionmentioning
confidence: 99%